Effectiveness of Storage Time Formulation of Bacillus Thuringiensis Against Aedes aegypti Larvae (Linnaeus, 1757) - Melanie Melanie; Mia Miranti Rustama; Inriyani Sintia Sihotang; Hikmat Kasmara (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
Aedes aegypti is known as the main vector of dengue fever in Indonesia which causes a high number of deaths and become an outbreak every year. This disease is generally controlled by breaking the life cycle of mosquitoes with restricted breeds and using synthetic insecticides. So far biological agents from natural enemies and natural pathogens have been developed to anticipate the negative effects of synthetic insecticides. Bacillus thuringiensis is well known as entomopathogenic bacteria that can control various insect pests of cultivated plants and vector insects, such as Ae.aegypti. B. thuringiensis can form endospores that produced toxin to Ae.aegypti, while the advatages are safe against non-target organisms such as natural predators and parasites, safe for mammals and humans and do not pollute the environment. Effective duration of B. thuringiensis in infecting Ae. aegypti is an important thing to be studied, moreover it is important to know the effectiveness of the expired formulation on the market and the residual effect. This ensures that the use of B. thuringiensis remains safe and does not create new problems such as Ae. aegypti resistance. The experimental research was used bioassay method, toxicity test was performed B. thuringiensis expired and non expire as comparison at concentration 0 ppm (control), 0,3 ppm; 0.1 ppm; 0.07 ppm; 0.05 ppm; 0.03 ppm; 0.01 ppm. The parameters observed were mortality for 48 hours of toxicity test that results were indicated by LC 50, LC90 and recidual values. The results obtained were LC50 and LC formulations B.thuringiensis expired 0.305 ppm and 1.513 ppm much higher than the non expire LC50 and LC formulations of 0.0363 ppm and 0.8971 ppm. The recidual effect of expired B. thuringiensis on larvae Ae. Aegypti was only effective until day 12, whereas B. thuringiensis that non expire formulation was effectively until day 14.Keywords : Ae. aegypti, B. thuringiensis, mortality, recidual values, expired formulation